THE LIMITS OF RECOURSE TO FORCE IN THE CONTEXT OF CONTEMPORARY GEOPOLITICS - Sandra Sophie-Elise OLĂNESCU (Challenges of the Knowledge Society)
Recourse to force represents a highly controversial subject matter, given its political sensitivity, as well as the legal framework that authorizes it. At the present time, it has commonly been assumed that recourse to force is highly forbidden in International Law. However, modern history has shown that this rule is strictly a desiderate that may be unobserved in certain circumstances by states, with the tacit consent that the International Society has expressed through its inactiveness. Thus, are military interventions of foreign states within the territory of other states legitimate? If so, how can reasonable motives be regulated to legitimate such actions under International Law? In this context, is recourse to force infringing the notion of external sovereignty, that serves both at protecting the states’ identity and personality, as well as at preserving individuals from armed conflicts? The purpose of this paper is to find possible answers to these questions, considering the trends in contemporary geopolitics.